2009
DOI: 10.1111/j.1548-1433.2009.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Ecological Knowledge as Situated Practices: Understanding Fishers’ Knowledge in the Western Solomon Islands

Abstract: In this article, we draw on research among fisherfolk of Roviana Lagoon, Solomon Islands, to examine certain epistemological assumptions of the "indigenous knowledge" concept. We describe how approaches to knowledge in Roviana differ from prevailing models of knowledge that distinguish between cognitive aspects and other modalities of knowing. For many Roviana fishers, ecological knowledge is not analytically separated from the changing contexts of everyday activities such as navigating and fishing.Inspired by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 50 publications
0
87
0
2
Order By: Relevance
“…This is probably because indigenous and local environment knowledge refers to systems of knowledge based on traditional and cultural practices and spiritual beliefs. Not surprisingly, conceptualisations of indigenous knowledge are controversial and disputed among many social scientists, who consider that the use of the term indigenous conceals inequalities and a neo-colonialist view on knowledge (Lauer & Aswani, 2009).…”
Section: Environmental Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…This is probably because indigenous and local environment knowledge refers to systems of knowledge based on traditional and cultural practices and spiritual beliefs. Not surprisingly, conceptualisations of indigenous knowledge are controversial and disputed among many social scientists, who consider that the use of the term indigenous conceals inequalities and a neo-colonialist view on knowledge (Lauer & Aswani, 2009).…”
Section: Environmental Educationmentioning
confidence: 99%
“…Research on local, indigenous and traditional ecological knowledge has been approached through a traditional paradigm of knowledge (with important exceptions, e.g., García-Allut, 1999;Olsson & Folke, 2001;Crona, 2006;Berkes, 2009;Lauer & Aswani, 2009;Briggs, 2013 In-depth structured interviews and a few observations PPP tripartite and SDF frameworks means that the ecological knowledge of local users has often been limited to comparison with scientific knowledge and treated almost as its opposite, being hardly validated because of its situated nature. In line with Berkes (2009), who considers that instead of only capturing this knowledge as (scientifically validated) information, it should be investigated as 'ways of knowing'.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a growing number of anthropologists have found that these approaches and techniques constrain descriptions and obscure the hybrid and heterogeneous nature of indigenous or local knowledge and modes of understanding (see Spoon 2014, Carothers et al 2014. For example, as Lauer and Aswani (2009) note, "More research is needed to develop approaches and methods that can empirically record aspects of knowledge and understanding that are commonly ignored in indigenous knowledge studies," in order to, "more fully explore, comprehend, and appreciate indigenous people‛s lives and perspectives in a rapidly changing world (Lauer and Aswani 2009: 327)." In keeping with this call, many recent approaches to the study of knowledge converge on the recognition that knowledge is embedded in multiple systems of practice, beliefs, values, and power across all scales.…”
mentioning
confidence: 99%